Slot-die coating method in organic solar panel and evaluation in polluted air - Tohid Irani; Hedieh Deyhim (Sustinere: Journal of Environment and Sustainability, 2024)
Renewable energy sources and pollution have a direct effect on each other. Solar panels development could enhance the adoption of green energy sources and contribute to a cleaner environment. Today's third generation organic photovoltaic panels (OPVs) offer good efficiency, low fabrication costs, and can be produces rapidly using slot-die coating methods. These advantages make OPVs increasingly attractive for broadening solar energy consumption. Therefore, related studies are being conducted to achieve this goal. This study aimed to evaluate real-world performance of OPVs in polluted air by testing a fully slot-die-coating OPV module in Tehran’s polluted environment, specifically at four air quality control stations. The results showed a power conversion efficiency (PCE) of 6.3% under standard test condition (STC) and maximum power output of 0.189 W in 5×6 cm module, which include ITO/PET, PEI, P3HT-PCBM, PEDOT-PSS, and AGNW layers. Testing in polluted environment revealed a significant dicrease in current and maximum power (Pmax) due to reduced sunlight reaching the module’s surface. Pmax dropped to 0.0229 W at least polluted site in Masodieh Street and to 0.0173 W at the most polluted site in Shahr-e Rey Street.